ADHD: a critical update for educational professionals. (7th June 2017) - te Meerman, Sanne; Batstra, Laura; Grietens, Hans; Frances, Allen
ABSTRACT: A medical approach towards behavioural problems could make professionals without a medical background, like teachers and other educational professionals feel inapt. In this article, we raise six scientifically grounded considerations regarding ADHD, currently the most prevalent childhood psychiatric diagnosis. These "need to knows" show just how misguided and potentially stigmatizing current conceptualizations of unruly behaviour have become. Some examples are given of how teachers are misinformed, and alternative ways of reporting about neuropsychological research are suggested. A reinvigorated conceptual understanding of ADHD could help educational institutions to avoid the expensive outsourcing of behavioural problems that could also—and justifiably better—be framed as part of education's primary mission of professionalized socialization.